The Influence of Operational Costs on Operating Income and Interest Rates on Non-Performing Loans in Banking Companies listed on thei Indonesian Stock Exchange - Rani Safitri; Sulastri; Isni Andriana (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to analyze the effect of operational costs on operational income and interest rates on non-performingiloans in banking companies on the Indonesian Stock Exchange. iThe population in this study are banking companies on the Indonesia Stock Exchange for 2018 - 2022 with a totaliof 150 companies and a total sample of 30 companies. iThe sampling technique was purposive sampling. iThe data collection technique documentation is used from financial reports published on the IDX's official website, namely www.idx.co.id. iThe analysis used is multiple linear regression analysis with panel data. The results of this research show that operational costs on operational income have a significant positive effect on non-performing loans, This means that operational costs on operational income have not been able to minimize the level of non-performing loans, thus causing an increase in non-performing loans. while interest rates do not affect non-performing loans, which means that the interest rate position does not influence non-performing loans.